How the differential load induced by normal fault scarps controls the distribution of monogenic volcanism - Maccaferri, F; Rivalta, E.; ACOCELLA, Valerio (Geophysical Research Letters, 2015)
Understanding shallow magma transfer and the related vent distribution is crucial for volcanic hazard. Here we investigate how the stress induced by topographic scarps linked to normal faults affects the distribution of monogenic volcanoes at divergent plate boundaries. Our numerical models of dyke propagation below a fault scarp show that the dykes tend to propagate toward and erupt on the footwall side. This effect, increasing with the scarp height, is stronger for dykes propagating underneath the hanging wall side and decreases with the distance from the scarp. A comparison to the East African Rift System, Afar and Iceland shows that (1) the inner rift structure, which shapes the topography, controls shallow dyke propagation; (2) differential loading due to mass redistribution affects magma propagation over a broad scale range (100-105-m). Our results find application to any volcanic field with tectonics- or erosion-induced topographic variations and should be considered in any volcanic hazard assessment.